2020
DOI: 10.1051/e3sconf/202017604001
|View full text |Cite
|
Sign up to set email alerts
|

Field interpretation of earth remote sensing data and ground field surveys in the Republic of Kazakhstan, Kostanay region in the pre-sowing season

Abstract: The aim of the research is to carry out field and office work on conducting a sub-satellite survey on test sites of the Kostanay region of the Republic of Kazakhstan. Grain-sowing districts of the Kostanay region were selected as the objects of examination: Karabalyk, Fedorov, Mendykara, Uzunkol, Sarykol, Altynsarin, Kostanay, Denisov, Karasu, Taranov, Zhitikara, Auliekol, Kamysty, Naurzum. The determination of the reserves of productive soil moisture in the 0-100 cm layer by control points (100 points) carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In our previous works (Abuova et al, 2019;Ismuratov et al, 2020;Nugmanov et al, 2018), we applied remote sensing studies to various agricultural crops in Northern Kazakhstan. It was shown that remote sensing allows it to evaluate to evaluate potential for obtaining different soil and producing different various on and effect of different factors on crop performance.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous works (Abuova et al, 2019;Ismuratov et al, 2020;Nugmanov et al, 2018), we applied remote sensing studies to various agricultural crops in Northern Kazakhstan. It was shown that remote sensing allows it to evaluate to evaluate potential for obtaining different soil and producing different various on and effect of different factors on crop performance.…”
Section: Discussionmentioning
confidence: 99%